2023
DOI: 10.1002/anie.202218959
|View full text |Cite
|
Sign up to set email alerts
|

Design of Drug Efficacy Guided by Free Energy Simulations of the β2‐Adrenoceptor

Abstract: G-protein-coupled receptors (GPCRs) play important roles in physiological processes and are modulated by drugs that either activate or block signaling. Rational design of the pharmacological efficacy profiles of GPCR ligands could enable the development of more efficient drugs, but is challenging even if highresolution receptor structures are available. We performed molecular dynamics simulations of the β 2 adrenergic receptor in active and inactive conformations to assess if binding free energy calculations c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…A comparison between simulations with and without these restraints (Figure C) revealed a significant accuracy gain when the restraints were used, confirming the validity of our underlying reasoning. Notably, the restraints ensured that the separation between agonists and antagonists was close to ΔΔ G = 0, an outcome that had not been achieved by similar approaches in previous studies with tight restraints outside the binding pocket. , Overall, our protocol has proven to be effective in accurately separating agonists and antagonists.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…A comparison between simulations with and without these restraints (Figure C) revealed a significant accuracy gain when the restraints were used, confirming the validity of our underlying reasoning. Notably, the restraints ensured that the separation between agonists and antagonists was close to ΔΔ G = 0, an outcome that had not been achieved by similar approaches in previous studies with tight restraints outside the binding pocket. , Overall, our protocol has proven to be effective in accurately separating agonists and antagonists.…”
Section: Resultsmentioning
confidence: 81%
“…Notably, the restraints ensured that the separation between agonists and antagonists was close to ΔΔG = 0, an outcome that had not been achieved by similar approaches in previous studies with tight restraints outside the binding pocket. 17,18 Overall, our protocol has proven to be effective in accurately separating agonists and antagonists.…”
Section: ■ Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Finally, in a more recent study, the ligand efficacy of closely related β 2 -AR compounds was also explored using RBFE calculations. 115 RBFE calculations have gained increased confidence in driving SBDD for GPCR targets through their successful implementation on supporting the ligand binding elucidation hypothesis and through studies where they retrospectively confirmed previous experimental/computational results. There are successful examples of prospective applications to GPCR SBDD and retrospective studies probing the limits of applicability of RBFE calculation, for example for fragmentbased drug design (FBDD), as described later in this section.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the present study, with an aim to understand the process of receptor-mediated G-protein activation, we investigate the rst steps of this reaction sequence for the β 2 -adrenoceptor-Gs (β 2 AR-Gs) signaling system, for which there is a wealth of experimental data that can expand further interpretation 5,10,16,22,23,24,25 . The β 2 AR is a family A GPCR that primarily couples to Gs to enhance intracellular cAMP levels 26 , hence regulating important physiological responses such as smooth muscle relaxation and bronchodilation 27 .…”
Section: Introductionmentioning
confidence: 99%